Confirmation of an He I evaporating atmosphere around the 650-Myr-old sub-Neptune HD 235088 b (TOI-1430 b) with CARMENES - Orell-Miquel, Jaume; Lampón, Manuel; López-Puertas, M.; Mallorquín, Manuel; Murgas, F.; Peláez-Torres, A.; Pallé, Enric; Esparza-Borges, Emma; Sanz-Forcada, J.; Tabernero, H. M.; Nortmann, Lisa; Nagel, E.; et al. (Astronomy and astrophysics, 2023)
HD 235088 (TOI-1430) is a young star known to host a sub-Neptune-sized planet candidate. We validated the planetary nature of HD 235088 b with multiband photometry, refined its planetary parameters, and obtained a new age estimate of the host star, placing it at 600-800 Myr. Previous spectroscopic observations of a single transit detected an excess absorption of He I coincident in time with the planet candidate transit. Here, we confirm the presence of He I in the atmosphere of HD 235088 b with one transit observed with CARMENES. We also detected hints of variability in the strength of the helium signal, with an absorption of −0.91 ± 0.11%, which is slightly deeper (2σ) than the previous measurement. Furthermore, we simulated the He I signal with a spherically symmetric 1D hydrodynamic model, finding that the upper atmosphere of HD 235088 b escapes hydrodynamically with a significant mass loss rate of (1.5−5) × 1010 g s−1 in a relatively cold outflow, with T = 3125 ±375 K, in the photon-limited escape regime. HD 235088 b (Rp = 2.045 ± 0.075 R⊕) is the smallest planet found to date with a solid atmospheric detection - not just of He I but any other atom or molecule. This positions it a benchmark planet for further analyses of evolving young sub-Neptune atmospheres.
Gesehen am 23.04.2024
Online veröffentlicht: 05. September 2023